Recreating esthetics in severely mutilated primary teeth - Case reports - R Ganesh; Sonu Bose; Joyson Moses (Wolters Kluwer Medknow Publications, 2012)
The restoration of severely caries primary teeth is a challenge to the pediatric dentist. The premature loss of these teeth can cause mastication and phonetic alterations, unaesthetic appearance and aberrant habits. This may lead to malocclusion and psychological problems affecting the self-esteem of the child. Hence importance should be given for restoration and maintenance of these teeth. Here we explain the present clinical cases of successful restoration using omega shape stainless steel wire of such severely mutilated deciduous teeth.